Developing Preschool Language Surveillance Models - Cumulative and Clustering Patterns of Early Life Factors in the Early Language in Victoria Study Cohort - Eadie, Patricia; Levickis, Penny; McKean, Cristina; Westrupp, Elizabeth; Bavin, Edith L.; Ware, Robert S.; Gerner, Bibi; Reilly, Sheena (Frontiers in Pediatrics, 2022)
Background Screening and surveillance of development are integral to ensuring effective early identification and intervention strategies for children with vulnerabilities. However, not all developmental skills have reliable screening processes, such as early language ability. Method We describe how a set of early life factors used in a large, prospective community cohort from Australia are associated with language abilities across the preschool years, and determine if either an accumulation of risk factors or a clustering of risk factors provide a feasible approach to surveillance of language development in preschool children. Results There were 1208 children with a 7-year language outcome. The accumulation of early life factors increased the likelihood of children having low language skills at 7-years. Over a third of children with typical language skills (36.6%) had ≤ two risks and half of the children with low language (50%) had six or more risks. As the number of factors increases the risk of having low language at 7-years increases, for example, children with six or more risks had 17 times greater risk, compared to those with ≤ two risks. Data collected from 1910 children at 8- to 12-months were used in the latent class modelling. Four profile classes were identified. The largest class was developmentally enabled with a supportive home learning environment (56.2%, n=1073). The second class was vulnerable, both developmentally and in their home learning environment (31.2%, n=596); the third class was socially disadvantaged with a vulnerable home learning environment (7.4%, n=142); the final class featured maternal mental health problems and vulnerable child socio-emotional adjustment (5.2%, n=99). Compared to developmentally enabled children, the risk of low language at 7-years was greater for children in the three other classes. Conclusion The cumulative and cluster risk analyses demonstrate the potential to use developmental surveillance to identify children within the first years of life who are at risk of language difficulties. Importantly, parent-child interaction and the home learning environment emerged as a consistent cluster. We recommend they be adopted as the common focus for early intervention and universal language promotion programs.